{{ item.displayTitle }}

No history yet!

Student

Teacher

{{ item.displayTitle }}

{{ item.subject.displayTitle }}

{{ searchError }}

{{ courseTrack.displayTitle }} {{ statistics.percent }}% Sign in to view progress

{{ printedBook.courseTrack.name }} {{ printedBook.name }} The Quadratic Formula has many computations and, therefore, many places where errors can occur. In this case we can see that the first time $b=-7$ was replaced in the Quadratic Formula, one of the negatives was dropped. $x = 2a-b±b_{2}−4ac $ In our quadratic, $3x_{2}−7x−6=0,$ we have $a=3,$ $b=-7,$ and $c=-6.$ So the first substitution of $-b$ should have looked like $-(-7).$

Let's substitute correctly and solve.

Interestingly enough, the answers with the error are just different signs of the actual solutions.